2022
DOI: 10.1186/s12893-022-01471-9
|View full text |Cite
|
Sign up to set email alerts
|

Frailty index is useful for predicting postoperative morbidity in older patients undergoing gastrointestinal surgery: a prospective cohort study

Abstract: Background Many assessment tools have been used to identify frail surgical patients. This study was designed to explore the prediction value of the frailty index (FI) for postoperative morbidity in older patients undergoing elective gastrointestinal surgery. Methods Between January 2019 and September 2020, we conducted a prospective study in our hospital, and patients aged over 65 years were enrolled. The FI assessment was conducted by two speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…However, the eFI has previously been used and validated in patients undergoing surgical procedures and has been associated with adverse post operative outcomes across a number of surgical specialties. [19][20][21][22] This study contributes to the broader literature on frailty in the cardiovascular field, and highlight's the importance of a comprehensive geriatric assessment in the management of older adults with AF.…”
Section: Discussionmentioning
confidence: 90%
“…However, the eFI has previously been used and validated in patients undergoing surgical procedures and has been associated with adverse post operative outcomes across a number of surgical specialties. [19][20][21][22] This study contributes to the broader literature on frailty in the cardiovascular field, and highlight's the importance of a comprehensive geriatric assessment in the management of older adults with AF.…”
Section: Discussionmentioning
confidence: 90%
“…The survival advantage associated with LT persisted even in the matched cohort in our study. Other studies have shown a relatively long 5‐year survival of 66%−70% for elderly patients receiving LTs, compared to the median survival of 10−14 months in patients with early‐stage HCC not receiving any treatment, which conveys a clear survival benefit of an LT 5,17 . Previous studies comparing the early outcomes of LTs in young versus elderly patients did not show any significant difference in rates of vascular or biliary morbidity between the two groups, 17–20 with none of the studies demonstrating age as a predictor of early mortality.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have shown a relatively long 5‐year survival of 66%−70% for elderly patients receiving LTs, compared to the median survival of 10−14 months in patients with early‐stage HCC not receiving any treatment, which conveys a clear survival benefit of an LT 5,17 . Previous studies comparing the early outcomes of LTs in young versus elderly patients did not show any significant difference in rates of vascular or biliary morbidity between the two groups, 17–20 with none of the studies demonstrating age as a predictor of early mortality. The rates of the major indicators of postoperative outcome (rates of vascular and biliary complications) are not different irrespective of the age of the liver recipient, and these operations can safely be carried out in an elderly population.…”
Section: Discussionmentioning
confidence: 96%
“…Frailty studies have important roles in optimizing neurosurgical outcomes in Africa, as the frailty index was found to be useful in determining perioperative morbidity [24]. It's therefore important that research that focuses on generating a frailty index that will be specific for patients in different neurosurgical facilities across the continent be carried out to serve as guides for neurosurgeons in carefully selecting patients for surgeries and also preoperative counseling and consent taking.…”
Section: Importance Of Frailty In Africa Neurosurgical Practicementioning
confidence: 99%